2022
DOI: 10.1002/ange.202200946
|View full text |Cite
|
Sign up to set email alerts
|

Engineering MoOx/MXene Hole Transfer Layers for Unexpected Boosting of Photoelectrochemical Water Oxidation

Abstract: The development of semiconductor photoanodes is of great practical interest for the realization of photoelectrochemical (PEC) water splitting. Herein, MXene quantum dots (MQD) were grafted on a BiVO 4 substrate, then a MoO x layer by combining an ultrathin oxyhydroxide oxygen evolution cocatalyst (OEC) was constructed as an integrated photoanode. The OEC/ MoO x /MQD/BiVO 4 array not only achieves a current density of 5.85 mA cm À 2 at 1.23 V versus a reversible hydrogen electrode (vs. RHE), but also enhances p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…26 Among these materials, two-dimensional MXene with high conductivity, good hydrophilicity, and a large specific surface area has been investigated for PEC water splitting recently. 27,28 For example, Ye et al fabricated a Fe 2 O 3 /MXene heterojunction to suppress the interfacial charge recombination and confirmed that the high hole-mobility MXene could serve as a hole transfer mediator. 29 Qin et al synthesized a CdS/MXene composite for highefficiency hydrogen generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Among these materials, two-dimensional MXene with high conductivity, good hydrophilicity, and a large specific surface area has been investigated for PEC water splitting recently. 27,28 For example, Ye et al fabricated a Fe 2 O 3 /MXene heterojunction to suppress the interfacial charge recombination and confirmed that the high hole-mobility MXene could serve as a hole transfer mediator. 29 Qin et al synthesized a CdS/MXene composite for highefficiency hydrogen generation.…”
Section: Introductionmentioning
confidence: 99%
“…These photothermal materials have been widely applied in photothermal therapy and catalysis, which generally convert optical energy into thermal energy in one of the three ways, namely, plasmonic localized heating, nonradiative relaxation, and thermal vibration in molecules . Among these materials, two-dimensional MXene with high conductivity, good hydrophilicity, and a large specific surface area has been investigated for PEC water splitting recently. , For example, Ye et al fabricated a Fe 2 O 3 /MXene heterojunction to suppress the interfacial charge recombination and confirmed that the high hole-mobility MXene could serve as a hole transfer mediator . Qin et al synthesized a CdS/MXene composite for high-efficiency hydrogen generation .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an impressive photocurrent density of 6.73 mA cm −2 at 1.23 V RHE in the KBi electrolyte (pH 9.5) that approached the theoretical value has been reported using phosphorus–oxygen bonded FeNi catalysts ( 42 ). MXene quantum dots and MoO x combined with oxyhydroxide cocatalyst loaded on BiVO 4 achieved a current density of 5.85 mA cm −2 at 1.23 V RHE with an enhanced photostability ( 43 ). An alternative approach is the combination of BiVO 4 with a more conductive layer (e.g., WO 3 ) in the form of the heterojunction, leading to the improved PEC performance and high solar energy to hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Specifically, these catalysts can efficiently utilize surface-reaching photo-generated holes from the bulk BiVO 4 and minimize the reaction overpotential, accelerating the surface reaction kinetics. 33 Among various co-catalysts, VIII metal (Ni, Co, and Fe) oxides or layered double hydroxides have attracted worldwide interest. 34,35 For example, Gong et al demonstrated that introducing Co 3 O 4 co-catalysts on BiVO 4 could achieve a charge separation efficiency of up to 77% in the bulk and 47% on the surface of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Specically, these catalysts can efficiently utilize surface-reaching photogenerated holes from the bulk BiVO 4 and minimize the reaction overpotential, accelerating the surface reaction kinetics. 33 Among various co-catalysts, VIII metal (Ni, Co, and Fe) oxides or This journal is © The Royal Society of Chemistry 2023…”
Section: Introductionmentioning
confidence: 99%